Acute Bacterial Meningitis in Nigerian Children Beyond Neonatal Period - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Childhood acute bacterial meningitis remains a significant cause of morbidity and mortality especially in developing countries. The pattern of both sporadic and epidemic cases of meningitis has been known to change from place to place even in the same country or geographical region.Streptococcus pneumoniae, Haemophilus influenzae type b, andNeisseria meningitidisare the predominant causes of community-acquired bacterial meningitis beyond the neonatal period.